A Fresh Approach to Tackle School Learner Pregnancies: Applying the Framework for Safe and Successful Schools - Tshiamo N Ramalepa (Disease and Health Research: New Insights Vol. 9, 2024)
This chapter presents a framework that proposes strategies to manage school learner pregnancy using the theory for safe and successful schools. The framework’s concepts emphasize a modern approach to running the health system of unique schools by educating and preparing all learners to achieve their highest potential irrespective of their health condition. This can be achieved by creating safe and inviting school environments, and using collaborative multi-tier systems that involve all relevant stakeholders. The framework further highlights the importance of creating such environments by working towards integrating services that address the academic, emotional, social, psychological, and mental health needs of school learners and teachers. The two main approaches that can be used to promote safe and successful schools include the use of the comprehensive integrated school improvement model and the best practices for safe and successful schools. Effective, thorough, and cooperative efforts that involve the commitment of all school personnel, the education department, the health department, the community, and other pertinent stakeholders are necessary to establish school safety and a healthy learning environment. To promote learning and prevent pregnancy and its problems, schools must implement methods that are reliable and efficient. They also need to give these strategies enough time to be put into practice and to be continuously evaluated. This chapter recommends strategies for fostering a welcoming environment for pregnant learners without compromising the high academic and social expectations for all learners. Furthermore, the education department needs to establish a thorough, age-appropriate sex education curriculum that begins in primary school and lasts into secondary school. Policies should be unambiguous, inclusive, and supportive of pregnant learners’ rights to complete education. Moreover, schools should provide learners access to confidential health services through collaborations with community health nurses, to assist in the early detection and monitoring of pregnancies. Lastly, teachers and school personnel should receive thorough training on how to support pregnant learners. Contribution: This chapter will highlight an innovative approach to prevent and manage learner pregnancies in schools using the theory for safe and successful schools. It will also contribute to the development of evidence-based learner pregnancy prevention and management initiatives.